The scale factor's 3 since 12 and 4 can be divided by 3 and -6 and -2 can also be divided by 3.
There is not enough information to answer :(
?
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
y(x) = x^(1/3)+7
y(-8)=(-8)^(1/3)+7=5
y(-1)=(-1)^(1/3)+7=6
y(1)=(1)^(1/3)+7=8
y(8)=(8)^(1/3)+7=9
----------------------------------------------------
Define the numbers
----------------------------------------------------
Let the first even number be x
1st even number = x
2nd even number = x + 2
3rd even number = x + 4
----------------------------------------------------
Form the equation and solve
----------------------------------------------------
x + x + 2 + x + 4 = -6
3x + 6 = -6
3x = - 12
x = -4
----------------------------------------------------
Find the numbers
----------------------------------------------------
1st even number = x = -4
2nd even number = x + 2 = -4 + 2 = -2
3rd even number = x + 4 = -4 + 4 = 0
----------------------------------------------------
Answers: The numbers are -4, -2 and 0
----------------------------------------------------